Aerobic granular sludge for complex heavy metal-containing wastewater treatment: characterization, performance, and mechanisms analysis - Liu, Chong; Shen, Yao; Li, Yuguang; Huang, Fengguang; Wang, Shuo; Li, Ji (Frontiers in Microbiology, 2024)
Complex heavy metal (HM)-containing wastewater discharges pose substantial risks to global water ecosystems and human health. The aim of this study was to evaluate the characterization, performance and mechanism of aerobic granular sludge (AGS) in the treatment of complex HM-containing wastewater, specifically with respect to Cu(II), Ni(II), and Cr(III). The results showed that AGS efficiently eliminated Cu(II), Ni(II), and Cr(III) by the orchestrated mechanisms of ion exchange, three-layer extracellular polymeric substances (EPS) adsorption [soluble microbial products EPS (SMP-EPS), loosely bound EPS (LB-EPS), tightly bound EPS (TB-EPS)], and inner-sphere adsorption; notably, almost 100% of Ni(II) was removed. Three-layer EPS adsorption was the dominant mechanism through which the HM were removed, followed by ion exchange and inner-sphere adsorption. SMP-EPS and TB-EPS were identified as the key EPS fractions for adsorbing Cr(III) and Cu(II), respectively, while Ni(II) was adsorbed evenly on SMP-EPS, TB-EPS, and LB-EPS. Moreover, the rates at which the complex HM penetrated into the granule interior and their affinity for EPS followed the order Cu(II) > Ni(II) > Cr(III). Ultimately, addition of complex HM stimulated microorganisms to excrete massive phosphodiesterases (PDEs), leading to a pronounced decrease in cyclic diguanylate (c-di-GMP) levels, which subsequently suppressed EPS secretion due to the direct linkage between c-di-GMP and EPS. This study unveils the adaptability and removal mechanism of AGS in the treatment of complex HM-containing wastewater, which is expected to provide novel insights for addressing the challenges posed by intricate real wastewater scenarios.